Religion and the Spiritual Crisis of Modern Human Being in the Perspective of Huston Smith`S Perennial Philosophy - Riki - Saputra (Graduate Program of Pontianak Institute of Islamic Studies, 2016)
This work is based on the assumption that modern human has undergone a multidimensional crisis. This crisis needs a timely response and an urgent solution, for if we neglect it, it will become worse and can destabilize the life of mankind globally. I refer to the work of Huston Smith on perennial philosophy to find its essence as an attempt to find solution for overcoming the modern men`s crisis. This is a library research using the philosophical hermeneutics method. The paper shows that, firstly, perennial philosophy has a characteristic of metaphysics, which try to find a fundamental basis for both immanent and transcendent of all things, psychology which depicts the common sameness in human and ethics as a goal in human life. Secondly, what is meant by human spiritual crisis is a condition where human neglected even destroyed the godhead character within themselves. Thirdly, the answer made by Huston smith`s Perennial Philosophy concerning human spiritual crisis include that the spiritual crisis of modern human being are seen from the tunnel metaphore, in which the basement is scientism, the left wall is education, media as the roof, and the right wall the law. The spiritual crisis of modern human being as a failure of post-modernism has a similiraty with modernism way of seeing this world as the only true reality, although there is different in approach between the two. Religious mysticism that was offered by Huston smith has a perenialistic tone. The pluralistic attitude found among humankind has to be rooted in an esoteric level within each religion. Smith`s perennial philosophy is very relevant to the condition of Indonesia, which therefore has sackeled by a rigid theological dogmatism. Religion should be an endeavor for human being to find a more exalted living.